The Political Dynamics of Sustainable Coffee: Contested Value Regimes and the Transformation of Sustainability. (11th August 2015) - Levy, David; Reinecke, Juliane; Manning, Stephan
ABSTRACT: The global coffee sector has seen a transformation towards more 'sustainable' forms of production, and, simultaneously, the continued dominance of mainstream coffee firms and practices. We examine this paradox by conceptualizing the underlying process of political corporate social responsibility (PCSR) as a series of long‐term, multi‐dimensional interactions between civil society and corporate actors, drawing from the neo‐Gramscian concepts of hegemony and passive revolution. A longitudinal study of the evolution of coffee sustainability standards suggests that PCSR can be understood as a process of challenging and defending value regimes, within which viable configurations of economic models, normative‐cultural values, and governance structures are aligned and stabilized. Specifically, we show how dynamics of moves and accommodations between challengers and corporate actors shape the practice and meaning of 'sustainable' coffee. The results contribute to understanding the political dynamics of CSR as a dialectic process of 'revolution/restoration', or passive revolution, whereby value regimes assimilate and adapt to potentially disruptive challenges, transforming sustainability practices and discourse.